The use of radioactive iodine-125 seed localization in patients with non-palpable breast cancer. Issue 4 (April 2015) - van der Noordaa, M.E.M.; Pengel, K.E.; Groen, E.; van Werkhoven, E.; Rutgers, E.J.Th.; Loo, C.E.; Vogel, W.; Vrancken Peeters, M.J.T.F.D.
Abstract Background Radioactive Seed Localization with a radioactive iodine-125 seed (RSL) and Radioguided Occult Lesion Localization with 99mTechnetium colloid (ROLL) are both attractive alternatives to wire localization for guiding breast conserving surgery (BCS) of non-palpable breast cancer. The aim of this study was to evaluate and compare the efficacy of RSL and ROLL. Methods We retrospectively analyzed 387 patients with unifocal non-palpable ductal carcinoma in situ (DCIS) or invasive carcinoma treated with BCS at the Netherlands Cancer Institute. In total 403 non-palpable lesions were localized either by RSL (N = 128) or by ROLL (N = 275). Primary outcome measures were positive margins and re-excision rates; the secondary outcome measure was weight of the specimen. Results Pre-operative mammography or ultrasound showed similar sizes of DCIS and invasive tumours in both RSL and ROLL groups. In the RSL group, more lesions were DCIS (58%) than in the ROLL group, where 32% of the lesions were pure DCIS. The proportions of focally positive margins (11% vs. 10%) and more than focally positive margins (9% vs. 9%) were comparable between the RSL and the ROLL group, resulting in the same re-excision rate in both RSL and ROLL groups (9% vs. 10%). For DCIS lesions, the specimen weight was significantly lower in the RSL group than in the ROLL group after adjusting for tumour size on mammography (12 g; 95% CI 2.6–21). Conclusion Margin status and re-excision rates were comparable for RSL and ROLL in patients with non-palpable breast lesions. Because of the significant lower weight of the resected specimen in DCIS, the feasibility of position verification of the I-125 seed and more convenient logistics, we favour RSL over ROLL to guide breast-conserving therapy.